SEX AND THE CITY: OBSERVATIONS ON HOMOSEXUAL MEN’S CRUISING SPACE IN A PUBLIC PARK OF DELHI - Bhairannavar, Kiran (ShodhKosh: Journal of Visual and Performing Arts, 2022)
In recent years, cruising sites have increasingly become deserted owing to factors such as the popularization of Internet-based dating and urban redevelopment projects, among others. The paper focuses on male homosexual cruising in a public park of Delhi. It aims to throw light on a once popular cruising site- now closed, focusing on the performative aspects of cruising and the ways in which men produced a queer space against the dominant spatial coding of the city. Using ethnographic methods of participant observation and conversational interviews with 18 men the study notes that the space of the park was central to the realisation of queer men’s lifeworlds. Men used various tactics to attract attention of other men and find sexual companionship, even as they tactically navigated the park space in reaction to the hostile heteronormative world around.